In Vitro Estimation of Tracheobronchial and Alveolar Doses Using Filters - Finlay, Warren H.; Farina, Dino J.; Tavernini, Scott; Martin, Andrew R. (Frontiers in Drug Delivery, 2022)
To date, in vitro estimation of doses delivered by an inhaler to the different major regions of the lung has required combining particle size measurements of the inhaled aerosol with in silico deposition models. Such a two step process is labor and time intensive. Here, we describe instead the development of an apparatus that allows direct estimation of regional lung deposition by measurement of doses collected on purpose-built metal grid filters that mimic tracheobronchial deposition efficiency. Placing these filters downstream of the Alberta Idealized Throat and upstream of a final filter allows collection of doses depositing in the extrathoracic, tracheobronchial and alveolar regions. Artificial electrostatic deposition on the metal tracheobronchial filters is prevented by a custom inline electrostatic neutralizer. We use the resulting apparatus to estimate regional deposition with a variety of dry powder inhalers during realistic, time-varying inhalation maneuvers and three pMDIs with a constant flow rate of 30 L/min. These results are compared to those obtained with the traditional two step approach that combines cascade impaction with a regional deposition model. Good agreement is found between the two approaches, indicating that the present direct method may be an efficient, time-saving alternative method for in vitro estimation of regional lung doses.